Two-Step Growth of Goethite from Ferrihydrite - Burleson, David J; Penn, R. Lee (Langmuir, 2006)
Goethite (α-FeOOH) is an antiferromagnetic iron oxyhydroxide that is often synthesized by precipitation from homogeneous, aqueous solution followed by aging. This paper addresses goethite growth by phase transformation of six-line ferrihydrite nanoparticles to goethite followed by oriented aggregation of the goethite primary particles. Data tracking goethite nanocrystal growth as a function of pH, temperature, and time is presented. In general, goethite growth by oriented aggregation is faster at higher pH and at higher temperature even as growth by coarsening becomes increasingly important as pH increases. In addition, particle size measurements demonstrate that the primary nanoparticles grow by Ostwald ripening even as they are being consumed by oriented aggregation. Finally, the use of a microwave anneal step in the preparation of the precursor six-line ferrihydrite nanoparticles substantially improves the homogeneity of the final goethite product. Final goethite nanoparticles are unaggregated, acicular crystals in the tens of nanometers size range. These particles may be ideal for mineral liquid crystal and magnetic-recording media applications.